Personal Data as Subject of Contracts for the Supply of Digital Content and Digital Services – Selected Aspects - Miščević, Nikolina B.; Savčić, Sanja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
This paper focuses on contracts for the supply of digital content and digital services in which one party undertakes to provide digital content or a digital service, while the other party, instead of paying a monetary sum, agrees to provide personal data. In recent decades, with the development of new technologies, the internet, and social networks, awareness of the value of personal data has significantly increased. This value is not only tied to the importance of personal data for the individual’s identity and privacy protection but also to its immense economic potential in the modern world, often referred to in the literature as “a key currency of the new millennium.” The recognition of the value and profitability that entities gain from processing consumer data has contributed to a paradigm shift. Previously, online services that collected user data—such as social media account creation—were perceived as free. Consequently, the EU Proposal for a Directive on certain aspects of contracts for the supply of digital content and digital services introduced the concept of personal data as “counter-performance” provided by consumers in exchange for digital content or services. Although the term “counter-performance” was ultimately omitted from the final text of the Directive, it is undeniable that the provision of personal data constitutes the subject matter of these contracts. However, the unique nature of this contractual subject raises various legal questions, such as the feasibility of valuing personal data, the legal capacity required to conclude such contracts, the rights consumers acquire in the event of contract termination, and the impact of personal data protection rules on the permissibility and validity of these agreements. Additionally, there are concerns about the legal consequences of terminating a contract when personal data has already been provided. This paper will explore some of these issues, particularly focusing on personal data as consideration and the legal capacity required to conclude contracts of this nature.